Le déclin des lieux touristiques en question - Philippe Duhamel; Philippe Violier (Bulletin de l’Association de Géographes Français)
Since a long time, models have been mobilized to explain the crisis of use of tourist places, models mobilized to announce the future misfortunes and the actions to take to avoid this. In reality, these models feed on received ideas and negative images of tourism, while history and the detailed analysis of situations show the remarkable durability and adaptability of tourist places considered as an open socio-spatial system.